(untitled) (World Bulletin of Social Sciences, 2024)
Language and culture are considered an integral part of the field of linguistics, and with the help of language, a person understands the world and expresses it. It is the formation of his culture and behavior. In this article, language and culture are considered objects of linguistics study, and it can be seen whether they are interrelated or separate.